(untitled) (Fiep Bulletin - online, 2014)
Introduction: Spinal cord injury can occur traumatically occurring as a consequence the loss of spinal cord neurons and axonal connections between brain region and peripheral effectors, leading to alterations of sensory, motor, autonomic, and different degrees of functional dependency. The scale of the Functional Independence Measure is one of the most used tools in assessing the functional capacity of individuals with spinal cord injury. Methods: The present research it is characterized by being a research -type clinical qualitative and quantitative, cross-sectional type cause and effect, there were 13 individuals with spinal cord injur, where the data were collected at the rehabilitation center of Assisi School Gurgacz - FAG in the city of Cascavel - PR from May to August of 2013 through interviews , using the scale Functional Independence Measure ( FIM ). Objective: To assess the level of functional independence of patients after spinal cord injury. Results: There was a predominance of males with 12 individuals and one individual for females. As the functional independence level 5 subjects C3 T1 will scale MIF was ranked modified dependence , two individuals with injury level T5 T6 will be rated modified dependence, 2 and 4 individuals T7 T10 S1 will complete / modified independence . Conclusion: The assessment by the FIM scale allows you to check the level of independence of patients and to quantify the effective gain after rehabilitation. Additionally , you can modify the treatment strategy neurofuncionnal when needed.